Effects of Eimeria maxima infection doses on growth performance and gut health in dual-infection model of necrotic enteritis in broiler chickens - Goo, Doyun; Choi, Janghan; Ko, Hanseo; Choppa, Venkata Sesha Reddy; Liu, Guanchen; Lillehoj, Hyun Soon; Kim, Woo Kyun (Frontiers in Physiology, 2023)
The objective of this study was to investigate the effects of the different doses of Eimeria maxima (EM) oocysts on growth performance and intestinal health in broiler chickens challenged with a dual infection model of necrotic enteritis (NE) using EM and NetB + Clostridium perfringens (CP). A total of 432 fourteen-d-old male Cobb 500 broiler chickens were divided into 6 groups with 6 replicates each. The six different groups were as follows: Control, non-challenged; T0 + , challenged with CP at 1 × 10 9 colony forming unit; T5K + , T0 + + 5,000 EM oocysts; T10K + , T0 + + 10,000 EM oocysts; T20K + ; T0 + + 20,000 EM oocysts; and T40K + ; T0 + + 40,000 EM oocysts. The challenge groups were orally inoculated with EM strain 41A on d 14, followed by NetB + CP strain Del-1 on 4 days post inoculation (dpi). Increasing EM oocysts decreased d 21 body weight, body weight gain , feed intake (linear and quadratic, P < 0.001), and feed efficiency (linear, P < 0.001) from 0 to 7 dpi. Increasing EM oocysts increased jejunal NE lesion score and intestinal permeability on 5, 6, and 7 dpi (linear, P < 0.05). On 7 dpi, increasing the infection doses of EM oocysts increased jejunal CP colony counts (linear, P < 0.05) and increased fecal EM oocyst output (linear and quadratic, P < 0.001). Furthermore, increasing the infection doses of EM oocysts decreased the villus height to crypt depth ratios and the goblet cell counts (linear, P < 0.05) on 6 dpi. Increasing EM oocysts downregulated the expression of MUC2, B 0 AT, B 0,+ AT, PepT1, GLUT2, AvBD3 and 9, LEAP2, and TLR4, while upregulating CLDN1, CATHL3, IL-1β, IFN-γ, TNFSF15, TNF-α, IL-10, and Gam56 and 82 on 6 dpi (linear, P < 0.05). Additionally, increasing EM oocysts decreased Pielou's evenness and Shannon's entropy (linear, P < 0.01). In conclusion, increasing the infection doses of EM significantly aggravated the severity of NE and exerted negative impact on intestinal health from 5 to 7 dpi. 1 Introduction